Teucrium francoi M. Seq., Capelo, J.C. Costa & R. Jardim, a new species of Teicrium gr. scorodonia (Lamiaceae) from Madeira - Sequeira, M.M. (2013)
The species formerly recognized as Teucrium scorodonia in Madeira is here described as new: Teucrium francoi M. Seq., Capelo, J.C. Costa & R. Jardim. Morphologically close to species of Teucrium gr. scorodonia [T. scorodonia L., T. pseudoscorodonia Desf., T. siculum (Raf.) Guss. and T. kotschyanum Poech], it exhibits, nonetheless, some distinct diagnostic characters. The indumentum density and type of hairs of T. francoi are clearly distinct from those of related species, as are the shape and dimensions of the leaves and bracts, calyx, and corolla, which are all taken as taxonomically significant diagnostic features. A diagnosis and a distribution map are presented for this new species. Morphology, ecology, biogeography, and conservation issues are discussed. Teucrium francoi, which is an endemic from Madeira (Portugal), is to be found mostly in the scope of the association Teucrio francoi– Origanetum virentis J.C. Costa, Capelo, Jardim, Sequeira, Lousã & Rivas-Martínez, but also occurs in somewhat humid habitats, such as open stands of Rosa mandonii Déségl. associated with small streams